World War II historical reenactment in Poland : the practice of authenticity - Baraniecka-Olszewska, Kamila (2022)
Introduction – Re-history: the subject of experience in historical reenactment – The experience of the past – The quest for authenticity – The legitimisation of authenticity – Past/present, here/there: reenactors' space-time – Impression – An authentic problem: women from the past – Can everything be reenacted? – Concluding remarks